Fabrication of capacitive absolute pressure sensors by thin film vacuum encapsulation on SOI substrates. (4th August 2016) - Belsito, Luca; Mancarella, Fulvio; Roncaglia, Alberto
Abstract: The paper reports on the fabrication and characterization of absolute capacitive pressure sensors fabricated by polysilicon low-pressure chemical vapour deposition vacuum packaging on silicon-on-insulator substrates. The fabrication process proposed is carried out at wafer level and allows obtaining a large number of miniaturized sensors per substrate on 1  ×  2 mm 2 chips with high yield. The sensors present average pressure sensitivity of 8.3 pF/bar and average pressure resolution limit of 0.24 mbar within the measurement range 200–1200 mbar. The temperature drift of the sensor prototypes was also measured in the temperature range 25–45 °C, yielding an average temperature sensitivity of 67 fF K −1 at ambient pressure.